2021
DOI: 10.1177/00018392211058426
|View full text |Cite
|
Sign up to set email alerts
|

Storytelling as a Tool for Vicarious Learning among Air Medical Transport Crews

Abstract: Learning vicariously from the experiences of others at work, such as those working on different teams or projects, has long been recognized as a driver of collective performance in organizations. Yet as work becomes more ambiguous and less observable in knowledge-intensive organizations, previously identified vicarious learning strategies, including direct observation and formal knowledge transfer, become less feasible. Drawing on ethnographic observations and interviews with flight nurse crews in an air medic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 88 publications
(117 reference statements)
0
17
0
Order By: Relevance
“…Thus in reaction to others’ inquiries, transgressors began to develop and share narratives about their transgressions with non-transgressors. As these responses became longer, we observed that they shared similarities with the storytelling narratives in which organizational scholars have become increasingly interested (Boje, 1991, 1995, 2001; Myers, 2022). Consistent with scholarship on storytelling, transgressors formed their narratives to provide social accounts (Scott and Lyman, 1968; Sitkin, Sutcliffe, and Reed, 1993; Orbuch, 1997; Cobb, Stephens, and Watson, 2001; Skarlicki, Folger, and Gee, 2004) of the transgression to explain to others why the transgression happened.…”
Section: Resultsmentioning
confidence: 77%
“…Thus in reaction to others’ inquiries, transgressors began to develop and share narratives about their transgressions with non-transgressors. As these responses became longer, we observed that they shared similarities with the storytelling narratives in which organizational scholars have become increasingly interested (Boje, 1991, 1995, 2001; Myers, 2022). Consistent with scholarship on storytelling, transgressors formed their narratives to provide social accounts (Scott and Lyman, 1968; Sitkin, Sutcliffe, and Reed, 1993; Orbuch, 1997; Cobb, Stephens, and Watson, 2001; Skarlicki, Folger, and Gee, 2004) of the transgression to explain to others why the transgression happened.…”
Section: Resultsmentioning
confidence: 77%
“…Moreover, as interview subjects engage with the researcher, the subject as storyteller is recreating experiences through an encounter with a listener. This provides an opportunity for the interviewer to derive lessons from that experience even though not having directly observed the traumatic experience (Myers, 2021). The numerous interview stories referred to above provided an abundance of data for qualitative analysis using a textual approach (Gephart, 1993) where written material serves as "text" that is embedded with creative interpretations of the author.…”
Section: Methodological Approachcollecting Data From Episodes Of Vica...mentioning
confidence: 99%
“…To introduce a critical viewpoint for the commemoration of the Ocean Ranger, I emphasize dramaturgy's ability to identify opportunities for storytelling, impression management and remembrance (Boje et al, 2004;Corrigan and Rixon, 2017;D'Cruz, 2022). Research about vicarious interaction often places its interest in the stories instead of the storytelling process (Myers, 2021). However, dramaturgical critique may be (Goffman, 1963) which discusses how the social status of persons can be systemically reduced in our minds, and in the concept of Total Institutions (Goffman, 1962) where the mental state of psychiatric patients (and the institutionalized identity of the hospital itself) is questioned.…”
Section: Investigating Vicarious Traumamentioning
confidence: 99%
See 1 more Smart Citation
“…Organizational learning directs search by giving information helpful for forming construal and determining response ( Argote and Greve, 2007 ). In the long run, organizational responses are learned and retained through processes such as storytelling ( Myers, 2022 ), routine formation ( Bresman, 2013 ), and job creation ( Miner, 1990 ). In the short run, information from the environment shapes construal processes and influences the response.…”
Section: Implications For Psychology Researchmentioning
confidence: 99%